ANALISIS MAKNA REFERENSIAL DI APLIKASI X/TWITTER: STUDI KASUS AKUN SELEBTWEET DANTE (@SKIPBERAT) - Putri, Della Eka; Prayogi, Rahmat (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Dante on the Twitter/X platform. The focus of the research is to understand how words, phrases, and slang used in the tweets contain direct references to tangible objects, phenomena, and real events. This study employs a qualitative approach with a descriptive method, where the data consist of tweets selected based on their relevance to real-world references. Data analysis was conducted using content analysis by considering the context of each tweet and its relation to the referenced reality. The results show that out of all the data analyzed, there are 21 instances of referential meaning in the form of objects, 3 in the form of phenomena, and 16 in the form of events. Additionally, Dante’s tweets contain slang and abbreviations that carry specific meanings, serving as expressions and interactions with his followers. This study confirms that each word or phrase in the tweets contains referential meaning reflecting objects, psychological states, or real events, making understanding these meanings essential for accurately interpreting the conveyed messages. The findings are expected to provide insights into the use of referential meaning in digital communication and help understand user interaction and expression on social media.